链条谐波传动中刚轮齿廓曲线方程的研究 - 宋冠英; 陈树昌 (Jixie chuandong)
The harmonic drive is regarded as a great breakthrough of the mechanical drive. But the harmonic gear drive has some insurmountable defects. This paper introduces a new type of harmonic drive--the harmonic chain drive. And for the first time, this paper establishes the profile equation of the rigid gear on the basic of differential geometry and mesh theory.